The Effectiveness of the Career Guidance Module to Improve Career Maturity for Children with Special Needs in Inclusive Vocational High Schools - Wati, Laras Ambar; Gunarhadi, Gunarhadi; Asrowi, Asrowi (Jurnal Pendidikan dan Pengajaran, 2021)
This research is conducted based on children with special needs in Vocational High Schools, which has no good career maturity. Moreover, there are no basic career materials for children with special needs in the Vocational High Schools in Surakarta. Therefore, this research aims to develop the teaching materials in the form of a career guidance module to improve career maturity for children with special needs in the Inclusive Vocational High Schools in Surakarta. The method used in this research is Research and Development (RnD) research. The data analysis technique used in this research is the categorization formula. The research finding showed that the developed module had been appropriately stated to be used according to the test result by both experts and practitioners' validators. Meanwhile, the effectiveness test result showed a score improvement of children with special needs compared to the previous pre-tests and post-tests.